592. CLINICAL EVALUATION OF A HYPERSPECTRAL IMAGING SYSTEM FOR MINIMALLY INVASIVE SURGERY (HSI-MIS). (24th September 2022) - Thomaßen, Madeleine T; Köhler, Hannes; Maktabi, Marianne; Pfahl, Annekatrin; Chalopin, Claire; Gockel, Ines; Moulla, Yusef
Abstract: Hyperspectral Imaging (HSI) provides surgeons intraoperative colored images of abdominal organgs detecting the perfusion and oxygenation. Limiting factors such as missing colour video, camera size, and long acquisition times have been overcome in the first CE-certified HSI-System for Minimally-Invasive Surgery (HSI-MIS; TIVITA® Mini Endoscopy Edition, Diaspective Vision GmbH, Am Salzhaff, Germany). This system was evaluated in-vivo during surgery and compared with an HSI-System for Open Surgery (TIVITA® Tissue, Diaspective Vision GmbH, Am Salzhaff, Germany). Hyperspectral imaging was performed with both the HSI-MIS and the HSI-System for Open Surgery at the Region of Interest. 19 patients undergoing gastroenterologic resections were included in the study. The images acquired with the HSI-MIS were registered onto the images from the open HSI system, and spectra, as well as parameter images, were pixel-wise compared. Violin plots were created for Tissue Oxygen Saturation (StO2), Near-Infrared Perfusion Index (NIR PI), Tissue Water Index (TWI) and Organ Hemoglobin Index (OHI). The raw data was analyzed using a partial least squares (PLS) and compared with the parameters as calculated by the original software The MAE results for the in-vivo evaluation were: StO2: 17.4% ± 7.6%, NIR PI: 16.3 ± 9.4, OHI: 14.3 ± 4.5, and TWI: 18.3 ± 7.8. The results obtained by PLS were StO2: 11.1% ± 3.9% (improved by 36%), NIR PI: 9.5 ± 5.8 (improved by 42%), OHI: 10.7 ± 2.7 (improved by 25%) and TWI: 9.6 ± 4.3 (improved by 48%) Laparoscopic hyperspectral imaging during minimally invasive procedures shows promising results. Parameter deviations might be attributable to technical differences and on how the parameters are calculated. The PLS method has shown significant improvement compared to the original calculation.